Humor Dakwah KH. Anwar Zahid dalam Menumbuhkan Kesehatan Mental - Nenden Sri Hayati; Diandi Nur Hakim; Zahrah Isnaini (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2022)
Humans are individual and social creatures who always live side by side and need other people. Both as individual and social beings in human daily life cannot be separated from the existence of various problems. The problems faced by humans are not only physical problems but also problems related to the mind or soul which are also important studies. The problems faced by humans, if left unchecked, will cause pressure and result in mental health problems. The research method used in writing this journal is qualitative by analyzing the existing literature. From the results of the analysis, it is found that one way to overcome the pressure of the problems faced by humans is with humor. One form of the application of humor is in da'wah activities, where da'wah here acts as a medium for distributing humor. Keywords: humor, da'wah, mental health